Conditional quenching: a detailed look at the SFR−density relation at z ∼ 0.9 from ORELSE. Issue 4 (4th February 2019) - Tomczak, Adam R; Lemaux, Brian C; Lubin, Lori M; Pelliccia, Debora; Shen, Lu; Gal, Roy R; Hung, Denise; Kocevski, Dale D; Le Fèvre, Olivier; Mei, Simona; Rumbaugh, Nicholas; Squires, Gordon K; et al.
Abstract: We present a study of the star formation rate (SFR)–density relation atz ∼ 0.9 using data drawn from the Observations of Redshift Evolution in Large Scale Environments (ORELSE) survey. We find that SFR does depend on environment, but only for intermediate-stellar mass galaxies (10 10.1 < M * /M⊙ < 10 10.8 ) wherein the median SFR at the highest densities is 0.2–0.3 dex less than at lower densities at a significance of 4σ. Galaxies that are more/less massive than this have SFRs that vary at most by≈ 20 per cent across all environments, but show no statistically significant trend. We further split galaxies into low-redshift (z ∼ 0.8) and high-redshift (z ∼ 1.05) subsamples and observe nearly identical behaviour. We devise a simple toy model to explore possible star formation histories for galaxies evolving between these redshifts. The key assumption in this model is that star-forming galaxies in a given environment-stellar mass bin can be described as a superposition of two exponential time-scales (SFR ∝ e − t /τ ): a long−τ time-scale with τ = 4 Gyr to simulate 'normal' star-forming galaxies, and a short-τ time-scale with free τ (between 0.3 ≤ τ/Gyr ≤ 2) to simulate galaxies on a quenching trajectory. In general, we find that galaxies residing in low/high environmental densities are more heavily weighted to the long-τ/short-τ pathways, respectively, which we argue is a signature of environmental quenching. Furthermore, for intermediate-stellar mass galaxies this transition begins at intermediate-density environments suggesting that environmental quenching is relevant in group-like haloes and/or cluster infall regions.